12 men of Christmas [videorecording (DVD)] - Sanford, Arlene; Chenoweth, Kristin; Hopkins, Josh, 1970-; Chlumsky, Anna (20th Century Fox Home Entertainment, 2010)
Hilarious story about baring it all for a cause. When New York publicist E.J. Baxter loses both her job and her fiance at the office Christmas party, she does what anyone would do, she takes a job in Montana! Now, to help the local search-and-rescue station raise funds, E.J. must convince 12 men to pose naked for a calendar. And soon, she finds herself wanting to make room in her own calendar for one of the hunky rescuers!